Rheumatology and functional genome analysis in East Asia. Issue 1 (28th December 2021) - Fujio, Keishi
Abstract: Rheumatic diseases differ in severity and outcome across ethnic groups. Although genetic predisposition is an important factor influencing the development of rheumatic diseases, genomic data to date have been accumulated mainly in Europeans. However, East Asia has become an influential center for genetic studies worldwide, and there is also a growing need for a functional genome database for East Asians. Expression quantitative trait locus data for immune cell subsets can be extremely useful in interpreting the function of disease‐associated genetic polymorphisms. The development of a functional genome database for East Asians is expected to make a significant contribution to the understanding and stratification of the pathogenesis of rheumatic diseases in this population in the future.